Minimally invasive monitoring of chronic central venous catheter patency in mice using digital subtraction angiography (DSA) - Negrão de Figueiredo Miller, Giovanna; Kirschner, Stefanie; Brockmann, Marc Alexander (PLOS ONE, 2015)
Background Repetitive administration of medication or contrast agents is frequently performed in mice. The introduction of vascular access mini-ports (VAMP) for mice allows long-term vascular catheterization, hereby eliminating the need for repeated vessel puncture. With catheter occlusion being the most commonly reported complication of chronic jugular vein catheterization, we tested whether digital subtraction angiography (DSA) can be utilized to evaluate VAMP patency in mice. Methods Twenty-three mice underwent catheterization of the jugular vein and subcutaneous implantation of a VAMP. The VAMP was flushed every second day with 50 μL of heparinized saline solution (25 IU/ml). DSA was performed during injection of 100 μL of an iodine based contrast agent using an industrial X-ray inspection system intraoperatively, as well as 7±2 and 14±2 days post implantation. Results DSA allowed localization of catheter tip position, to rule out dislocation, kinking or occlusion of a microcatheter, and to evaluate parent vessel patency. In addition, we observed different ante- and retrograde collateral flow patterns in case of jugular vein occlusion. More exactly, 30% of animals showed parent vessel occlusion after 7±2 days in our setting. At this time point, nevertheless, all VAMPs verified intravascular contrast administration. After 14±2 days, intravascular contrast injection was verified in 70% of the implanted VAMPs, whereas at this point of time 5 animals had died or were sacrificed and in 2 mice parent vessel occlusion hampered intravascular contrast injection. Notably, no occlusion of the catheter itself was observed. Conclusion From our observations we conclude DSA to be a fast and valuable minimally invasive tool for investigation of catheter and parent vessel patency and for anatomical studies of collateral blood flow in animals as small as mice.